Correction: Reaching adolescents with health services: Systematic development of an adolescent health check-ups and wellbeing programme in Ghana (Y-Check, Ghana). - Benedict Weobong; Franklin N Glozah; Hannah B Taylor-Abdulai; Eric Koka; Nancy Addae; Stanley Alor; Kid Kohl; Prerna Banati; Philip B Adongo; David A Ross (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0304465.].